THE RELATIONSHIP OF WOMEN'S STEREOTYPE AND MASCULINITY THROUGH THE STUDY OF THE MAIN CHARACTER IN THE NOVEL MOANA BY SUZANNA FRANCES - Denisa Yunita; Agnes Setyowati H.; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2020)
The main topic of this research is the relationship of stereotypes and masculinity of woman which is discussed based on a study of the main character in the novel Moana by Suzanna Francis. The research process uses intrinsic elements: characters, settings, conflicts, irony, and symbol, as well as extrinsic elements: gender, masculinity-femininity, stereotypes and symbolic violence. This research uses descriptive analytical methods and literature study techniques that produce stereotype findings that cause masculine trait of characters in the main character. The main character, suffered gender injustice of stereotypes and symbolic violence which can be seen from her fathers prohibition to let her go outside the reef. Upon the agreement, the main character was encouraged to go outside the reef by carrying out the mission of recovering and saving inhabitants of the village.Keywords: Masculine, stereotypes, gender injustice, symbolic violence, and woman.